Determinants of externally visible birth defects among perinatal deaths at Adama Comprehensive Specialized Hospital: a case-control study - Husen Aman; Seifadin Ahmad; Getahun Chala; Mekbeb Afework (BMC, 2024)
Abstract Background Birth defects (BDs) are the major causes of infant morbidity and mortality in both developed and developing countries. Regardless of their clinical importance, few studies on predisposing factors have been conducted in Ethiopia. However, due to a lack of advanced diagnostic materials, we only considered the externally visible BDs. Objective To assess the determinants of externally visible birth defects among perinatal deaths at Adama Comprehensive Specialized Hospital. Methods A retrospective unmatched case-control study design was conducted from November 01 to 30, 2021. The sample size was determined by Epi Info version 7 software considering sample size calculation for an unmatched case-control study. A total of 315 participants (63 cases, and 252 controls) were selected by simple random sampling. Data were collected by an open data kit (ODK) and transported to a statical package for social sciences (SPSS) version 26 software for analysis. The bivariate followed by multivariable logistic regression analyses were done to determine the factors associated with the BD. Results This study showed that drinking alcohol during pregnancy (AOR = 6.575; 95% CI: 3.102,13.937), lack of antenatal care (ANC) follow-up during pregnancy (AOR = 2.794; 95% CI: 1.333, 5.859), having a history of stillbirth in a previous pregnancy (AOR = 3.967; 95% CI: 1.772, 8.881), exposure to pesticides during pregnancy (AOR = 4.840; 95% CI: 1.375, 17.034), having a history of BDs in a previous pregnancy (AOR = 4.853; 95% CI: 1.492, 15.788), and lack of folic acid supplementation during early pregnancy (AOR = 4.324; 95% CI: 2.062, 9.067) were significant determinants of externally visible BDs among perinatal deaths. Conclusion In this study, alcohol use, exposure to pesticides, and lack of folic acid supplementation during pregnancy were identified as the major determinants of externally visible BDs among perinatal deaths. Thus, health education regarding the associated factors of BDs and their preventive strategies should be given to pregnant mothers.